Pengaruh Persepsi Harga, Kualitas Produk terhadap Customer Satisfaction dan Keputusan Pembelian Konsumen - Mohammad Arief Baehaqi; Ida Bagus Nyoman Udayana; Henny Welsa (UNHI Press, 2022)
This research is survey research, with a quantitative approach. This study aims to determine the relationship between price perception variables, product quality variables, customer satisfaction, and consumer purchasing decisions by conducting a survey of Yogyakarta Indomaret customers. The sample was determined by the Slovin formula. The sampling technique used was simple accidental sampling using a questionnaire. The results of this study indicate that the Price Perception Variable has a significant effect on customer satisfaction based on the t experiment with a potential of 9.488 with a significance of <0.05 resulting in Ho being rejected and Ha accepted. Product quality has a significant effect on Customer Satisfaction because based on the t-test of 2,973 with a significance <0.05, this results in Ho being rejected and Ha being accepted. The customer satisfaction variable has a significant effect on consumer purchasing decisions as evidenced by the t-test with a value of 4.574 with a significance <0.05 which makes Ho rejected and Ha accepted. The price perception variable has a significant effect on consumer purchasing decisions as evidenced by the t-test of 2.127 with a significance <0.05 which resulted in Ho being rejected while Ha was accepted. Product quality has a significant effect on consumer purchasing decisions as evidenced by the t-test of 3.246 with a significance <0.05 which makes Ho rejected while Ha is accepted